2012
DOI: 10.1007/s12010-012-9685-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Klebsiella oxytoca: Evaluation of Methods for Extraction of Intracellular Metabolites Using UPLC/Q-TOF-MS

Abstract: The global pool of intracellular metabolites is a reflection of all the metabolic functions of an organism. In the absence of in situ methods capable of directly measuring metabolite pools, intracellular metabolite measurements need to be performed after an extraction procedure. In this study, we evaluated the optimization of technologies for generation of a global metabolomics profile for intracellular metabolites in Klebsiella oxytoca. Intracellular metabolites of K. oxytoca were extracted at the early stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…It allows measuring the levels of endogenous metabolites, thus enabling biomarker discovery [28]. The endogenous metabolites, including nucleic acids, lipids, amino acids, peptides, vitamins, organic acids, thiols, and carbohydrates, represent a valuable tool for detection of biomarkers for various diseases and monitoring disease progression [29, 30]. …”
Section: Biomarkers In Salivamentioning
confidence: 99%
“…It allows measuring the levels of endogenous metabolites, thus enabling biomarker discovery [28]. The endogenous metabolites, including nucleic acids, lipids, amino acids, peptides, vitamins, organic acids, thiols, and carbohydrates, represent a valuable tool for detection of biomarkers for various diseases and monitoring disease progression [29, 30]. …”
Section: Biomarkers In Salivamentioning
confidence: 99%
“…Similarly, washing steps were avoided to prevent metabolite loss but contamination of cell pellets with residual medium will be the same for each sample compared and medium-only controls were also run. Although the efficiency of extraction techniques is organism specific (Faijes et al 2007; Meyer et al 2013), comparative studies have shown cold methanol based methodologies to be among the most efficient for extracting a wide range of metabolites, in a broad spectrum of bacteria (Maharjan and Ferenci 2003; Park et al 2012). For this reason a cold methanol:chloroform based extraction protocol was adopted here (adapted from Overy et al (2005)).…”
Section: Resultsmentioning
confidence: 99%
“…subjected to the same quenching and extraction conditions, valid comparisons are possible. The efficacy of metabolite extraction techniques have been shown to be organism specific (8), but many comparative studies have shown cold methanol based methodologies to be the most efficient for extracting the broadest range of metabolites (8,9,10). For this reason a simple cold methanol based extraction protocol was adopted in our work, enabling high reproducibility and extraction of a broad range of metabolites (1,11).…”
Section: Introductionmentioning
confidence: 99%